2019
DOI: 10.1051/matecconf/201927201005
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of NFL-ZnWO4 for pseudocapacitor applications

Abstract: In this report, NFL-ZnWO4 was synthesized by a hydrothermal route and investigated for application in supercapacitors for the first time. The physical and chemical characterizations of the prepared nanomaterial were analyzed by SEM, EDS, XRD and XPS, respectively. Supercapacitors study of CV, GCD and EIS revealed that NFL-ZnWO4 exhibits good electrochemical properties. The high specific capacitance value of 107.7 F g-1 was achieved at 5 mV s−1. These findings demonstrated that ZnWO4 could be a promising electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The cubic point of the space group of ZnWO 4 /CB contains diffraction peaks at an angle of 2θ = 15.47°, 18.89°, 23.81°, 24.51°, 30.70°, 36.76°, 39.94°, 37.80°, 41.56°, 44.59°, 47.64°, 52.74°, 54.24°, 62.73°, 65.47°, 69.32°, 72.45° and 26.70° that corresponds to the (010), (100), (011), (110), (111), (120), (012), (102), (112), (030), (122), (020), (230), (023), (23) and (006) crystal planes, respectively (JCPDS-01-089-0447). These findings demonstrated that ZnWO 4 and CB diffraction peaks successfully appeared in the ZnWO 4 /CB composite composition without impurities, which confirms the formation of the ZnWO 4 /CB composite [ 37 ].…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The cubic point of the space group of ZnWO 4 /CB contains diffraction peaks at an angle of 2θ = 15.47°, 18.89°, 23.81°, 24.51°, 30.70°, 36.76°, 39.94°, 37.80°, 41.56°, 44.59°, 47.64°, 52.74°, 54.24°, 62.73°, 65.47°, 69.32°, 72.45° and 26.70° that corresponds to the (010), (100), (011), (110), (111), (120), (012), (102), (112), (030), (122), (020), (230), (023), (23) and (006) crystal planes, respectively (JCPDS-01-089-0447). These findings demonstrated that ZnWO 4 and CB diffraction peaks successfully appeared in the ZnWO 4 /CB composite composition without impurities, which confirms the formation of the ZnWO 4 /CB composite [ 37 ].…”
Section: Resultsmentioning
confidence: 69%
“…The relation between anodic peak current and scan rate is presented in Figure 7 C. Figure 7 D shows the linear regression equation is I pa (µA) = 0.1479 × (mVs −1 ) + 18.361 and the coefficient of ( R 2 = 0.9935). This finding implies that diffusion controls the electrocatalytic oxidation of CIP detected on the GCE/ZnWO 4 /CB surface [ 37 ].…”
Section: Resultsmentioning
confidence: 99%